Pengaruh Disiplin Kerja, Organizational Citizenship Behaviour terhadap Kinerja Prajurit dengan Motivasi sebagai Variabel Intervening - Mujanah, Siti; Anzeala, Sheisa; Suhardi, Suhardi (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2024)
This research aims to analyze the influence of Work Discipline and Organizational Citizenship Behavior (OCB) on the Performance of Indonesian Air Force Soldiers at Roesmin Nurjadin Pekanbaru Air Base with Work Motivation as an intervening variable. Data was collected from 108 Indonesian Air Force soldiers at Roesmin Nurjadin Air Base using a questionnaire, Likert scale 5. The data analysis technique used was multiple linear regression and Structural Equation Modeling (SEM-AMOS). The results of the research show that Work Discipline has a positive and significant effect on Soldier Performance, Work Discipline has a negative and significant effect on Work Motivation, Organizational Citizenship Behavior (OCB) has a positive and significant effect on Soldier Performance, Organizational Citizenship Behavior (OCB) has a positive and significant effect on Motivation Soldier Work, Work Motivation has a negative and insignificant effect on the Performance of Indonesian Air Force Soldiers at Roesmin Nurjadin Base Pekanbaru. The implication of this research is the importance of Work Discipline and Organizational Citizenship Behavior (OCB) to increase Soldiers' Work Motivation so that it can improve Soldiers' Performance